Formulation and Biological Evaluation of Some Selected Medicinal Plants for Anti-inflammatory Potential: Formulation and Biological Evaluation of Some Selected Medicinal Plants for Anti-inflammatory Potential - Kumar, Neelesh (International Journal of Pharmaceutical & Biological Archive, 2020)
Objective: The aim of the paper is to assess the anti-inflammatory potential of three medicinal plants using two rat models. Materials and Methods: Soxhlet extraction approaches utilized to separate the constituents of interest. Quantitative analysis has been performed to determine the total phenolic and flavonoid content. Three plants extract employed for the ointment formulation by addition of the extract of Artocarpus heterophyllus (AH), Murraya koenigii (MK), and Punica granatum (PG) in polyethylene glycol (PEG) ointment base, a blend of PEG 600 and PEG 4000, and ratio 7:3, respectively. Two rat models based on chemical induced animals employed for the anti-inflammatory potential. Results and Discussion: All three plants including AH Lam., MK Linn., and PG Linn. extracted for the major component and have shown the gallic acid and quercetin as major component for flavonoid and phenol content. The ointment formulation F3 has showed maximum inhibition (80.95%) at 50 mg/kg dose of carrageenan-induced edema and 83.33% inhibition at 100 mg/kg dose. The ointment formulation F3 has showed maximum inhibition (78.57%) at 50 mg/kg dose of histamine persuade edema and 83.33% inhibition at 100 mg/kg dose. F3 ointment formulation is better than the F2 and F1 formulation in inhibition and in all phases showing its reserve of kinins as well as arachidonic acid. Conclusion: Quantitative and pharmacological evaluation indicated that ointment formulations of AH, MK, and PG have exploit for anti-inflammatory activity. The normal extract has shown the least activity but ointment formulations have shown the better result. The ointment formulations containing plant extracts in 10% amount have better wound healing potential.